Early life history connectivity of Antarctic silverfish (Pleuragramma antarctica) in the Ross Sea - Brooks, Cassandra M.; Caccavo, Jilda Alicia; Ashford, Julian; Dunbar, Robert; Goetz, Kimberly; La Mesa, Mario; Zane, Lorenzo (Fisheries Oceanography, 2018)
A recent population hypothesis for Antarctic silverfish (Pleuragramma antarctica), a critical forage species, argued that interactions between life history and circulation associated with glacial trough systems drive circumpolar distributions over the continental shelf. In the Ross Sea, aggregations of eggs and larvae occur under fast ice in Terra Nova Bay, and the hypothesis predicted that dispersing larvae encounter outflow along the western side of Drygalski Trough. The outflow advects larvae towards the shelf-break, and mixing with trough inflow facilitates return toward the inner shelf. To examine the hypothesis, we compared samples of P. antarctica collected near Coulman Island in the outflow, along Crary Bank in the inflow, and a third set taken over the rest of the Ross Sea. We ruled out misidentification using an innovative genetic validation. Silverfish larvae comprised 99.5% of the catch, and the highest population densities were found in Drygalski Trough. The results provided no evidence to reject the population hypothesis. Abundance indices, back-calculated hatching dates, length distributions and growth were congruent with a unified early life history in the western Ross Sea, constrained by cryopelagic early stages in Terra Nova Bay. By contrast, a sample in the Bay of Whales revealed much smaller larvae, suggesting either a geographically separate population in the eastern Ross Sea, or westward connectivity with larvae spawned nearby by fish sourced from troughs upstream in the Amundsen Sea. These results illustrate how hypotheses that integrate population structure with life history can provide precise spatial predictions for subsequent testing.